2019
DOI: 10.1080/15384101.2019.1662678
|View full text |Cite
|
Sign up to set email alerts
|

Neutrophil extracellular traps induced by IL-8 aggravate atherosclerosis via activation NF-κB signaling in macrophages

Abstract: Here, we sought to explore the underlying role of interleukin (IL)-8 in neutrophil extracellular traps (NETs) formation during atherosclerosis (AS). The concentration of pro-inflammatory cytokines IL-8, IL-6 and IL-1β was determined by enzyme-linked immunosorbent assay (ELISA). NETs formation was evaluated by immunofluorescence and myeloperoxidase (MPO)-DNA complex ELISA. The mRNA levels of IL-8 and Toll-like receptor 9 (TLR9) were measured by quantitative real-time PCR (qRT-PCR). The phosphorylation levels of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
115
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 173 publications
(119 citation statements)
references
References 22 publications
4
115
0
Order By: Relevance
“…NETs contain several DAMPs that may be recognized by TLR4/9 [44]. TLR signals mediate the proinflammatory effect of NETs on several host cells [45,46]. Many reports have demonstrated that NETs could upregulate TLR9 expression in colon cancer cells and that TLR is an upstream regulator of COX2 expression [36,47,48].…”
Section: Discussionmentioning
confidence: 99%
“…NETs contain several DAMPs that may be recognized by TLR4/9 [44]. TLR signals mediate the proinflammatory effect of NETs on several host cells [45,46]. Many reports have demonstrated that NETs could upregulate TLR9 expression in colon cancer cells and that TLR is an upstream regulator of COX2 expression [36,47,48].…”
Section: Discussionmentioning
confidence: 99%
“…A commercially available kit (Q33120, USA, Thermo), which was described in a previous study,5 was used to determine the concentrations of serum cfDNA. All experimental procedures were carried out according to the manufacturer’s instructions.…”
Section: Methodsmentioning
confidence: 99%
“…Release of NETs is induced by CXCR2 activation via Src, extracellular signal-regulated kinase (ERK), and p38/MAPK signaling (86). The CXCL1-CXCR2 axis has been associated to NET formation and neutrophil degranulation in a model of deep vein thrombosis in mice (87) and in circulating and airway mucosal neutrophils of chronic obstructive pulmonary disease (COPD) patients.…”
Section: Role Of Chemokines In Neutrophil Effector Functionsmentioning
confidence: 99%